Modified graphite material and preparation method thereof, negative pole piece and lithium ion battery
By covering porous graphene tablets on the surface of graphite particles and introducing oxygen -containing energy groups to form a modified graphite material, solving the problem of energy density, cycle life and safety of graphite lithium ion batteries when fast charging, and achieve efficient efficiency Lithium ion transmission and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411606763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-28
AI Technical Summary
Existing graphite-based lithium-ion batteries are difficult to maintain high energy density, long cycle life and high safety during fast charging, mainly due to the slow electrochemical reaction process of graphite.
By covering porous graphene tablets on the surface of graphite particles, and introducing oxygen -containing energy groups on its surface to form modified graphite materials. This material is prepared by mechanical chemistry, and the ball mill is used to obtain a dense and flawed porous graphene tablets to improve the transmission rate and electrochemical performance of lithium ion.
Modified graphite materials significantly improve the multiplier performance, circulation performance, and storage performance of lithium -ion batteries, and can meet the needs of fast charging and long life while ensuring processing performance.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a modified graphite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have significant advantages such as high energy density, wide operating temperature range and long service life, and have become the most mature and widely used energy storage device.
[0003] Graphite is widely used in current lithium-ion batteries as an important negative electrode material. However, it is difficult for commercial graphite-based lithium-ion batteries to achieve fast charging without sacrificing the battery's energy density, cycle life and safety. This is because the slow electrochemical reaction process on the graphite surface greatly limits the fast charging of graphite. The fast charging technology of graphite mostly relies on surface and structural optimization. Surface treatment and structural optimization of graphite materials can also improve their charging performance. For example, the lithium ion diffusion rate is increased and volume changes are alleviated by doping, coating or creating a pore structure. Patent CN117199363A introduces a graphite negative electrode material, a preparation method, and a battery. The graphite negative electrode material includes a core composed of multiple graphite particles and a zwitterionic polymer coating layer coating the core. The graphite particles are coated with a resin material in the liquid phase and granulated by a spray drying process and then carbonized to form a granulated product with a hard carbon coating layer. The graphite negative electrode material prepared by this patent has the characteristics of high rate, but the hard carbon pore structure is complex and has poor affinity with the electrolyte. Therefore, the first coulombic efficiency and high-temperature storage performance of the material are poor, which makes it difficult to meet the performance requirements of commercial lithium-ion power batteries.
[0004] At present, exploring new battery chemistry based on traditional graphite materials is an important way to quickly realize fast-charging lithium-ion batteries. However, despite a lot of attempts and explorations by researchers, such as particle morphology design, coating, doping, etc., it is still difficult to simultaneously meet the high dynamics of the battery while taking into account the simple preparation process, good graphite particle processing performance, long cycle life and other various performances. In view of this, based on the current higher requirements for the fast-charging performance of lithium-ion battery negative electrode materials, it is of great practical significance to provide a graphite negative electrode material with a simple preparation method, excellent rate performance, cycle performance and processing performance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a modified graphite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery.
[0006] In a first aspect, the present invention provides a modified graphite material, comprising graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 0.1-10:100.
[0007] As a preferred technical solution of the present invention, the oxygen-containing functional group includes any one or more of a hydroxyl group, a carboxyl group, a carbonyl group, a keto group and an epoxy group.
[0008] As a preferred technical solution of the present invention, based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 0.05-2.8%.
[0009] As a preferred technical solution of the present invention, the average width of the ordered layered nano-domains of the porous graphene sheet is 4-20 nm.
[0010] As a preferred technical solution of the present invention, the average thickness of the ordered layered nano-domains of the porous graphene sheet is 0.2-2 nm.
[0011] As a preferred technical solution of the present invention, the carbon interlayer spacing of the porous graphene sheet is 0.34-0.46nm.
[0012] As a preferred technical solution of the present invention, the volume median particle size of the porous graphene sheet is 0.1-2 μm.
[0013] As a preferred technical solution of the present invention, the volume median particle size of the graphite particles is 5-25 μm.
[0014] As a preferred technical solution of the present invention, the volume median particle size of the modified graphite material is 8-16 μm.
[0015] As a preferred technical solution of the present invention, the graphite particles include graphitized particles of petroleum coke, oil-based needle coke, coal-based needle coke, asphalt coke or isotropic coke.
[0016] In a second aspect, the present invention provides a method for preparing the modified graphite material according to the first aspect, the preparation method comprising:
[0017] (1) ball milling a graphite source to obtain a porous graphene sheet;
[0018] (2) dispersing the porous graphene sheets, graphite particles and a binder in a solvent for granulation to obtain a modified graphite material precursor;
[0019] (3) Carbonizing and activating the modified graphite material precursor in sequence to obtain the modified graphite material.
[0020] As a preferred technical solution of the present invention, the rotation speed during ball milling is 120-900r / min.
[0021] As a preferred technical solution of the present invention, the ball milling time is 2-7h.
[0022] As a preferred technical solution of the present invention, the temperature during granulation is 140-550°C.
[0023] As a preferred technical solution of the present invention, the granulation time is 1-10 hours.
[0024] As a preferred technical solution of the present invention, the carbonization is carried out under an inert gas atmosphere, and the inert gas includes nitrogen and / or argon.
[0025] As a preferred technical solution of the present invention, the carbonization temperature is 400-1000°C.
[0026] As a preferred technical solution of the present invention, the carbonization time is 2-8h.
[0027] As a preferred technical solution of the present invention, the activation is carried out in the presence of deionized water, and the mass ratio of the deionized water inflow per minute to the modified graphite material precursor is 0.1-7.2:100.
[0028] As a preferred technical solution of the present invention, the activation temperature is 600-1200°C.
[0029] As a preferred technical solution of the present invention, the activation time is 1-4h.
[0030] As a preferred technical solution of the present invention, the mass ratio of the porous graphene sheets, graphite particles and binder is (0.1-8):(74-99.89):(0.01-18).
[0031] As a preferred technical solution of the present invention, the graphite source includes any one or more of expanded graphite, natural flake graphite, artificial graphite and recycled graphite.
[0032] As a preferred technical solution of the present invention, the binder includes any one or more of asphalt, phenolic resin, glucose, sucrose, soluble starch and cyclodextrin.
[0033] As a preferred technical solution of the present invention, the solvent includes deionized water and / or ethanol.
[0034] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the modified graphite material described in the first aspect or the modified graphite material prepared by the preparation method described in the second aspect.
[0035] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.
[0036] In a fifth aspect, the present invention provides a vehicle, comprising the lithium-ion battery described in the fourth aspect.
[0037] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:
[0038] 1. The modified graphite material provided by the present invention has a fast lithium ion transmission rate, high tap density, small specific surface area, high capacity, excellent rate performance and processing performance, and can effectively improve the rate performance, cycle performance and storage performance of lithium ion batteries.
[0039] 2. The present invention utilizes a mechanochemical method to prepare a porous graphene sheet coating layer with suitable density and flexibly adjustable defect density, and introduces oxygen-containing functional groups on the surface of the graphene sheet layer, which effectively improves the rate performance, gram capacity and cycle performance of the modified graphite material. The preparation method has a simple process, low cost, and readily available raw materials, and conventional production equipment can be used. DETAILED DESCRIPTION
[0040] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0043] At present, exploring new battery chemistry based on traditional graphite materials is an important way to quickly realize fast-charging lithium-ion batteries. However, despite a lot of attempts and explorations by researchers, such as particle morphology design, coating, doping, etc., it is still difficult to simultaneously meet various performance requirements such as high kinetics, simple preparation process, good graphite particle processing performance, and long cycle life. Therefore, based on the current higher requirements for the fast-charging performance of lithium-ion battery negative electrode materials, the embodiments of the present invention provide a modified graphite material and a preparation method thereof, a negative electrode sheet, and a lithium-ion battery.
[0044] First, the present invention provides a modified graphite material, which includes graphite particles and porous graphene sheets coated on the surface of the graphite particles, the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 0.1-10:100, such as 0.1:100, 0.5:100, 1:100, 2:100, 4:100, 6:100, 8:100, 10:100, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0045] The modified graphite material provided in the embodiment of the present invention has a fast lithium ion transmission rate, a high tap density, a small specific surface area, a high capacity, excellent rate performance and processing performance, and can effectively improve the rate performance, cycle performance and storage performance of lithium ion batteries. Specifically:
[0046] The modified graphite material provided in the embodiment of the present invention utilizes porous graphene sheets to coat graphite particles. On the one hand, the porous graphene sheets have vacancy defects, which are conducive to the rapid transmission of lithium ions, and the porous structure of the graphene sheets can improve the electrolyte wetting performance, thereby improving the rate performance and cycle performance of the material; on the other hand, the graphene sheets provided by the present invention are more dense, and coating the graphite particles as a coating layer can improve the tap density and reduce the specific surface area, thereby having good processing performance while having excellent cycle performance and storage performance; in addition, the surface of the porous graphene sheets has oxygen-containing functional groups, which can change the charge distribution on the graphite surface and provide additional capacitance to improve the electrochemical properties of the material, especially the rate performance and gram capacity. The synergistic effect of the above makes the prepared modified graphite material have high capacity, excellent rate performance and processing performance, and can effectively improve the rate performance, cycle performance and storage performance of lithium-ion batteries.
[0047] In some embodiments of the present invention, the oxygen-containing functional group includes any one or more of a hydroxyl group, a carboxyl group, a carbonyl group, a keto group and an epoxy group.
[0048] The surface of the modified graphite material provided by the embodiment of the present invention is rich in oxygen-containing functional groups, which can effectively improve the charge distribution on the graphite surface and can provide additional capacitance, thereby effectively improving the electrochemical properties of the modified graphite material.
[0049] In some embodiments of the present invention, the content of oxygen-containing functional groups is 0.05-2.8%, such as 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 2.8%, etc., based on the total mass of the modified graphite material as 100%. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable. When the content of oxygen-containing functional groups is within the range, the gram capacity of the modified graphite material can be more effectively increased, thereby effectively improving the electrochemical properties of the modified graphite material.
[0050] In some embodiments of the present invention, the average width La of the ordered layered nanodomains of the porous graphene sheet is 4-20 nm, such as 4 nm, 8 nm, 12 nm, 16 nm, 20 nm, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0051] In some embodiments of the present invention, the average thickness Lc of the ordered layered nanodomains of the porous graphene sheet is 0.2-2 nm, such as 0.2 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0052] The average width La and average thickness Lc (defect density) of the ordered layered nanodomains of the porous graphene sheet provided by the embodiment of the present invention are both small and can be flexibly adjusted. The edges of the porous graphene platelets have abundant active sites, which have the advantages of being fast and reversible and can be used as Li + The insertion or adsorption sites, and the ordered and straight structure of graphene flakes are conducive to the rapid transmission of lithium ions, thereby effectively improving the lithium ion transmission rate and further improving the rate performance of the material.
[0053] In some embodiments of the present invention, the carbon interlayer spacing Ln of the porous graphene sheet is 0.34-0.46 nm, such as 0.34 nm, 0.36 nm, 0.38 nm, 0.4 nm, 0.42 nm, 0.44 nm, 0.46 nm, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0054] The carbon layer spacing Ln of the porous graphene sheet provided in the embodiment of the present invention is small and can be flexibly adjusted. The compression of the carbon layer spacing can increase the packing density of the material, and has a denser macroscopic morphology. At the same time, it is beneficial to the optimization of the pore structure of the modified graphite material, thereby increasing the tap density of the modified graphite material and reducing the specific surface area. It has good processing performance (slurry dispersion performance, pole piece compaction density) while also having better cycle performance and storage performance.
[0055] In some embodiments of the present invention, the volume median particle size of the porous graphene sheet is 0.1-2 μm, such as 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0056] In some embodiments of the present invention, the volume median particle size of the graphite particles is 5-25 μm, such as 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0057] In some embodiments of the present invention, the volume median particle size of the modified graphite material is 8-16 μm, such as 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0058] In some embodiments of the present invention, the graphite particles include graphitized particles of petroleum coke, oil-based needle coke, coal-based needle coke, asphalt coke or isotropic coke.
[0059] Accordingly, an embodiment of the present invention provides a method for preparing a modified graphite material according to the first aspect, the method comprising:
[0060] (1) ball milling a graphite source to obtain a porous graphene sheet;
[0061] (2) dispersing the porous graphene sheets, graphite particles and a binder in a solvent for granulation to obtain a modified graphite material precursor;
[0062] (3) The modified graphite material precursor is carbonized and activated in sequence to obtain the modified graphite material.
[0063] The preparation method provided by the embodiment of the present invention has simple process, low cost, and readily available raw materials. The modified graphite material with excellent performance can be obtained by using conventional production equipment, which can effectively improve the rate performance of traditional graphite materials and avoid the risk of decreased processing performance and electrical performance caused by the introduction of electron-rich conductor graphene to the greatest extent. The prepared modified graphite material has high capacity and excellent rate performance, processing performance, cycle stability and other excellent properties. Specifically:
[0064] The preparation method provided in the embodiment of the present invention firstly mechanically ball-mills and cuts a graphite source and crushes it to obtain a porous graphene platelet with suitable density, flexibly adjustable defect density La and Lc and carbon interlayer spacing Ln. On the one hand, under the action of mechanical force, the graphite Sp 2 The hybrid conductive network introduces abundant active sites, which can act as Li + The insertion or adsorption sites, and the ordered and straight structure of graphene flakes are conducive to the rapid transmission of lithium ions on the surface of graphite particles, thereby effectively improving the rate performance of modified graphite materials. On the other hand, under the action of mechanical force, the carbon layer spacing of graphene sheets is compressed, thereby obtaining a higher packing density and a denser macroscopic morphology, which is conducive to the optimization of the morphology and pore structure of modified graphite materials, manifested in the increase of tap density and the reduction of specific surface area, while ensuring good processing performance (slurry dispersion performance, pole piece compaction density) while having better cycle performance and storage performance. In addition, after coating, the modified graphite material precursor is carbonized and activated in sequence. On the one hand, deionized water reacts with carbon particles to generate chemical bonds such as CO / C=O / CO-OH. The oxygen-containing functional groups can change the charge distribution on the graphite surface and provide additional capacitance to improve the electrochemical properties of the modified graphite material. On the other hand, the oxygen-affinity binder is carbonized and cured through heat treatment, and the porous graphene flakes with oxygen-containing functional groups are anchored on the surface of the graphite particles to enhance the bonding strength of the coating layer and form a stable coating structure, thereby improving the cycle performance of the negative electrode material under fast charging.
[0065] In some embodiments of the present invention, the rotation speed during ball milling is 120-900 r / min, such as 120 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, etc., preferably 360-900 r / min. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0066] In the embodiment of the present invention, porous graphene flakes with flexible and controllable morphology, particle size, carbon layer spacing, ordered nano-domain width and thickness are obtained by ball milling. When the rotation speed during ball milling is within the above range, the mechanical effects such as impact, compression, shearing, grinding, and stretching provided by ball milling can be used to obtain porous graphene flakes with small crystal size and richer micropores and edge structures, thereby exposing abundant active sites, which are beneficial to Li +The rapid transmission of lithium ions can be achieved, thereby improving the lithium ion transmission rate of the modified graphite material; at the same time, when the ball milling speed is within the above range, the pore structure can be more effectively optimized, and the electrolyte wetting performance of the obtained porous graphene sheet is greatly improved, thereby improving the rate performance and cycle performance of the modified graphite material.
[0067] In some embodiments of the present invention, the ball milling time is 2-7 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0068] When the ball milling time is within the above range, as time goes by, graphene flakes accumulate under the action of mechanical force, the specific surface area decreases, the stacking density increases significantly, and the carbon layer spacing decreases, which is conducive to forming a stable and relatively dense stacking structure. The microscopic morphology of the surface of the finished particles is improved, thereby improving the dispersion and processing performance of the material, and the compaction density of the pole piece using the modified graphite material is improved, avoiding the problems of low finished product tap density caused by excessive loose stacking, difficult dispersion of negative electrode slurry caused by large specific surface area, low ultimate compaction when the finished product is used as pole piece, and poor high temperature performance of the battery.
[0069] In some embodiments of the present invention, the temperature during granulation is 140-550° C., such as 140° C., 200° C., 300° C., 400° C., 500° C., 550° C., etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0070] In some embodiments of the present invention, the granulation time is 1-10 hours, such as 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0071] The present invention obtains a modified graphite material precursor after granulation, and then utilizes low-temperature carbonization and activation technology to improve the rate performance and gram capacity of the modified graphite material, while being able to obtain a stable coating layer with high bonding strength, thereby improving the long-term cycle performance of the modified graphite material.
[0072] In some embodiments of the present invention, the carbonization is performed under an inert gas atmosphere, and the inert gas includes nitrogen and / or argon.
[0073] In some embodiments of the present invention, the carbonization temperature is 400-1000° C., such as 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., etc. However, the present invention is not limited to the listed values, and other values not listed in the range are also applicable.
[0074] In some embodiments of the present invention, the carbonization time is 2-8 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0075] In some embodiments of the present invention, the heating rate during carbonization is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0076] When the carbonization temperature and time are within the above range, the binder can be carbonized and cured more completely, anchoring the graphene flakes on the surface of the graphite particles, effectively improving the bonding strength of the coating layer, forming a stable coating structure, and thereby improving the cycle performance of the modified graphite material under fast charging.
[0077] In some embodiments of the present invention, the modified graphite material precursor is placed in a rotary furnace for carbonization and activation, and the activation is carried out in the presence of deionized water. The mass ratio of the deionized water intake per minute to the modified graphite material precursor is 0.1-7.2:100, for example, 0.1:100, 1:100, 2:100, 4:100, 6:100, 7.2:100, etc.
[0078] When the amount of deionized water is within the above range, the degree of reaction between deionized water and carbon particles is more appropriate, and an appropriate amount of chemical bonds such as CO / C=O / CO-OH are generated on the surface of the graphene sheet, thereby effectively improving the charge distribution on the graphite surface and providing additional capacitance, thereby improving the electrochemical properties of the modified graphite material.
[0079] In some embodiments of the present invention, the activation temperature is 600-1200° C., such as 600° C., 800° C., 1000° C., 1200° C., etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0080] In some embodiments of the present invention, the activation time is 1-4 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0081] When the temperature and time during activation are within the above range, the degree of reaction between deionized water and carbon particles is more appropriate, and an appropriate amount of chemical bonds such as CO / C=O / CO-OH are generated on the surface of the graphene sheet, thereby effectively improving the charge distribution on the graphite surface and providing additional capacitance, thereby improving the electrochemical properties of the modified graphite material.
[0082] In some embodiments of the present invention, the heating rate during activation is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0083] In some embodiments of the present invention, the mass ratio of the porous graphene sheet, the graphite particles and the binder is (0.1-8):(74-99.89):(0.01-18), for example, 8:74:18, 5:80:15, 3:90:7, 1:95:4, 0.1:99.89:0.01, etc. However, the present invention is not limited to the listed values, and other values not listed within the range are also applicable.
[0084] In some embodiments of the present invention, the graphite source includes any one or more of expanded graphite, natural flake graphite, artificial graphite and recycled graphite.
[0085] In some embodiments of the present invention, the binder includes any one or more of asphalt, phenolic resin, glucose, sucrose, soluble starch and cyclodextrin.
[0086] In some embodiments of the present invention, the solvent includes deionized water and / or ethanol.
[0087] Accordingly, an embodiment of the present invention provides a negative electrode plate, which includes a modified graphite material.
[0088] Accordingly, an embodiment of the present invention provides a lithium-ion battery, and the lithium-ion battery includes a negative electrode plate.
[0089] Accordingly, an embodiment of the present invention provides a vehicle, which includes a lithium-ion battery.
[0090] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention will be further described in detail in conjunction with the embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its applications. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0091] If no specific techniques or conditions are specified in the examples, the conventional techniques or conditions in the art, or the techniques or conditions described in the literature, or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0092] Example 1
[0093] The present embodiment provides a modified graphite material and a preparation method thereof. The modified graphite material includes graphite particles and porous graphene sheets coated on the surface of the graphite particles. The surface of the porous graphene sheets has oxygen-containing functional groups. The mass ratio of the porous graphene sheets to the graphite particles is 1:84. Taking the total mass of the modified graphite material as 100%, the content of the oxygen-containing functional groups is 0.48%.
[0094] The preparation method comprises the following steps:
[0095] (1) 200 g of expanded graphite was placed in a planetary ball mill containing agate balls, with a material-ball ratio of 5:1, a rotation speed of 360 rpm, and a running time of 3 h. After the ball milling, a porous graphene sheet was obtained, and its physical and chemical parameters were tested: the volume median particle size D1 of the porous graphene sheet was 1.88 μm, the average width La of the ordered layered nanodomains was 18.8 nm, the average thickness Lc of the ordered layered nanodomains was 1.96 nm, and the carbon interlayer spacing Ln of the graphene sheet was 0.440 nm;
[0096] (2) The porous graphene sheets obtained in step (1) are ultrasonically dispersed in water to form a graphene solution (solid content 10%), and the graphene sheet solution, 7 μm needle coke primary particles and asphalt binder are placed in a horizontal reactor in a mass ratio of 10:84:6 for granulation at a granulation temperature of 200° C., a granulation time of 8 h, and a stirring speed of 80 rpm to obtain a modified graphite material precursor with a particle size of 14 μm.
[0097] (3) placing the modified graphite material precursor obtained in step (2) in a rotary kiln, introducing inert gas N2 at a flow rate of 80 sccm, a carbonization temperature of 600°C, a carbonization time of 6 hours, and a heating rate of 3°C / min; after the carbonization process is completed, the temperature is raised to 950°C, and DI (deionized water) is introduced for activation, the mass ratio of the water intake per minute of deionized water to the modified graphite material precursor is 2.4:100, the activation time is 2.5 hours, and the modified graphite material is obtained.
[0098] Example 2
[0099] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 1:84; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 0.22%;
[0100] The preparation method is the same as that in Example 1, except that the rotation speed during ball milling in step (1) is 120 rpm and the ball milling time is 2 h.
[0101] Example 3
[0102] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 1:84; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.62%;
[0103] The preparation method is the same as that in Example 1, except that the rotation speed during ball milling in step (1) is 720 rpm and the ball milling time is 5 h.
[0104] Example 4
[0105] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 1:84; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 2.74%;
[0106] The preparation method is the same as that in Example 1, except that the rotation speed during ball milling in step (1) is 900 rpm and the ball milling time is 7 h.
[0107] Example 5
[0108] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 1:84; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.32%;
[0109] The preparation method is the same as that in Example 1, except that the rotation speed during ball milling in step (1) is 600 rpm and the ball milling time is 6 h.
[0110] Example 6
[0111] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.58%;
[0112] The preparation method is the same as that of Example 5, except that in step (2), the needle coke primary particles are replaced by 10 μm petroleum coke primary particles, and the mass ratio of the graphene sheet solution, 10 μm petroleum coke primary particles and asphalt binder is 20:72:8.
[0113] Example 7
[0114] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.54%;
[0115] The preparation method is the same as that of Example 6, except that the binder in step (2) is replaced by phenolic resin.
[0116] Example 8
[0117] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 2.25%;
[0118] The preparation method is the same as that of Example 6, except that in step (3), the carbonization temperature is 400° C. and the carbonization time is 4 h.
[0119] Example 9
[0120] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 2.66%;
[0121] The preparation method is the same as that of Example 6, except that the activation time in step (3) is 4 hours.
[0122] Example 10
[0123] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 1:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.60%;
[0124] The preparation method is the same as that of Example 6, except that the mass ratio of the graphene sheet solution, 10 μm petroleum coke primary particles and asphalt binder is 10:72:18.
[0125] Embodiment 11
[0126] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 1.44%;
[0127] The preparation method is the same as that of Example 6, except that in step (3), the carbonization temperature is 1000° C. and the carbonization time is 8 h.
[0128] Example 12
[0129] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 2.8%;
[0130] The preparation method is the same as that of Example 6, except that the activation temperature in step (3) is 1200° C. and the activation time is 1 h.
[0131] Example 13
[0132] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 0.20%;
[0133] The preparation method is the same as that of Example 6, except that the activation temperature in step (3) is 600°C.
[0134] Embodiment 14
[0135] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 0.06%;
[0136] The preparation method is the same as that of Example 6, except that the activation temperature in step (3) is 400°C.
[0137] Embodiment 15
[0138] The present embodiment provides a modified graphite material and a preparation method thereof, wherein the modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, wherein the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 2:72; based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional groups is 0.24%;
[0139] The preparation method is the same as that of Example 6, except that the activation temperature in step (3) is 1500°C.
[0140] Comparative Example 1
[0141] This comparative example provides a modified graphite material and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that step (1) is not subjected to ball milling treatment, and only expanded graphite having the same volume median particle size D1 as the porous graphene sheet is used for steps (2) and (3).
[0142] Comparative Example 2
[0143] This comparative example provides a modified graphite material and a preparation method thereof. The preparation method is the same as that of Example 6, except that no activation treatment is performed after the carbonization process in step (3) is completed.
[0144] Application Examples
[0145] The modified graphite materials prepared in the examples and comparative examples are assembled into lithium-ion batteries, and the preparation method is as follows:
[0146] (1) Preparation of positive electrode sheet
[0147] Prepare positive electrode slurry and mix the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1O2, conductive agent (conductive carbon black), and binder (polyvinylidene fluoride) are mixed uniformly in an appropriate amount of solvent NMP according to a mass ratio of 96:2:2 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, and the double-sided surface density is 332.8g / m 2 Then it is dried, roll-pressed (density 2.62g / cc), and die-cut to obtain the positive electrode sheet.
[0148] (2) Preparation of negative electrode sheet
[0149] The negative electrode slurry was prepared by mixing the negative electrode active material, conductive filler (carbon black), and binder (styrene-butadiene rubber) in a mass ratio of 96:1:3 to obtain the negative electrode slurry. The negative electrode slurry was evenly coated on both sides of the negative electrode current collector copper foil, and the double-sided surface density was 145.3 g / m 2 The negative electrode active material is the modified graphite material prepared in the embodiment of the present invention or the comparative example, and then dried and rolled (density 1.60 g / cc). It is dried in an oven, and then cold pressed and cut to obtain the negative electrode sheet.
[0150] (3) Preparation of electrolyte
[0151] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.
[0152] (4) Preparation of isolation membrane
[0153] A polyethylene film with an aluminum oxide coating was selected as the separator.
[0154] (5) Preparation of lithium-ion batteries
[0155] The positive electrode sheet, separator, and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0156] It should be noted that the above-mentioned test lithium-ion battery is only an example listed for testing the performance of the negative electrode active material. The present invention is not limited to this type of battery. The raw materials (except the negative electrode active material), proportions, parameters and processes can be replaced by other conventional raw materials, proportions, parameters and processes in the art to form a battery different from the test lithium-ion battery.
[0157] Performance Testing
[0158] 1. Volume median particle size of powder
[0159] The laser diffraction particle size analyzer (MS3000) is used for measurement. The sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values of the scattering diagram at many angles and records these values for analysis. The Rayleigh scattering formula is used to calculate the scattering values to obtain the ratio of the volume of particles of each size level to the total volume, thereby obtaining the volume distribution of the particle size.
[0160] 2. Crystallite parameters of porous graphene flakes
[0161] The Rigaku Smartlab SE X-ray diffractometer was used for testing, and the XRD spectrum of the sample was refined using the jade analysis software. The average width La of the ordered layered nanodomains, the average thickness Lc of the ordered layered nanodomains, and the carbon interlayer spacing Ln of the graphene sheet were obtained using the Bragg equation and the Scherrer formula:
[0162] Ln=λ2sinθ 002 , Lc=Kλβ 002 cosθ 002 , La=1.84λ / (β 002 cosθ 002 );
[0163] Among them, θ 002 - diffraction angle of graphite 002 crystal plane, deg.;
[0164] The wavelength of λ-X-rays (0.1541),
[0165] K-correction factor (0.89);
[0166] β 002 - Half-peak width of graphite 002 crystal plane, rad.
[0167] 3. Test of oxygen-containing functional group content of modified graphite material particles
[0168] The Boehm titration method was used to test the possibility of the reaction between bases of different strengths and acidic oxides of different strengths on the surface of graphite powder materials. The content of oxygen-containing groups such as carboxyl, carbonyl and epoxy groups on the surface of modified graphite particle powder materials was calculated according to the different base consumption.
[0169] 4. Specific surface area of modified graphite material particles
[0170] The test was carried out using a McBee surface and porosity analyzer TriStar II Plus.
[0171] 5. Tap density of modified graphite material particles
[0172] The modified graphite material particles are tested for tap density using a tap density meter. The graduated cylinder filled with powder or particles is fixed on a mechanical vibration device. The vibration motor drives the mechanical vibration device to vibrate vertically up and down, and the number of vibrations is selected to be 1000 times.
[0173] 6. Gram capacity and first coulombic efficiency of modified graphite materials
[0174] Button test steps: In a dry argon environment, add LiPF6 to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (mass ratio of about 1:1:1), and mix evenly, wherein the concentration of LiPF6 is about 1.15 mol / L. The negative electrode active material, conductive carbon black, binder CMC and SBR obtained in the embodiment and comparative example are added to deionized water in a mass ratio of about 95.5:1.5:1.5:1.5, stirred to form a slurry, and a coating with a thickness of about 100 μm is formed by scraper coating, and dried at about 85°C in a vacuum drying oven for about 12 hours. In a dry environment, it is cut into discs with a diameter of 1 cm by a punching machine, and a metal lithium sheet is used as a counter electrode in a glove box. The isolation membrane selects a ceglard composite membrane, and an electrolyte is added to assemble a button battery. The battery is charged and discharged using the LAND series battery test to test its charge and discharge capacity, and its first coulomb efficiency is the ratio of the charge capacity to the discharge capacity. The charge and discharge rate is 0.05C and the voltage is 5mV~2V.
[0175] 7. Rate performance of lithium-ion batteries
[0176] The lithium-ion battery provided in the application example is discharged to 2.0V at 0.33C at 25°C, left standing for 5 minutes, charged to 3.75V at 4C, charged to 0.05C at a constant voltage and left standing for 5 minutes, and the ratio of the constant current charging capacity to the total capacity is the charging rate.
[0177] 8. Cycle performance of lithium-ion batteries
[0178] Test method: The lithium-ion battery provided in the application example is subjected to a 1C / 1C full charge and discharge cycle test at 45°C, with an operating voltage of 2.0V-3.75V, and the 1000cls capacity retention rate is recorded.
[0179] Among them, the volume median particle size D1 (μm), the average width La (nm) of the ordered layered nanodomains, the average thickness Lc (nm), and the carbon layer spacing Ln (nm) of the porous graphene sheets obtained in the examples and comparative examples are shown in Table 1:
[0180] Table 1
[0181]
[0182]
[0183] The volume median particle size D2, tap density, specific surface area, gram capacity, first coulomb efficiency of the modified graphite material particles, the charging rate of the lithium-ion battery, and the capacity retention rate of the cycle 1000cls are shown in Table 2:
[0184] Table 2
[0185]
[0186]
[0187] It can be found from Table 1 and Table 2 that the present invention uses a mechanochemical method to achieve precise cutting of expanded graphite to obtain porous graphene sheets with controllable microcrystalline morphology, particle size, carbon layer spacing, ordered nanodomain width and thickness. The present invention precisely coats the porous graphene sheets on the surface of graphite particles and modifies the surface of the porous graphene sheets with oxygen-containing functional groups, which can significantly improve the kinetic properties and cyclic stability of the modified graphite material.
[0188] From the comparison between Examples 1-5 and Comparative Example 1, it can be found that as the degree of mechanical grinding increases, the average width and average thickness of the ordered nanodomains of the graphene platelets decrease, which means that the disorder of the graphene platelets is significantly improved, thereby obtaining porous graphene platelets with rich exposed edges and rich active sites, which have small crystal size, rich micropores and edge structures, so that the introduced hole defects are beneficial to Li + Rapid transmission, so the dynamics of the material are significantly enhanced. By controlling the relative extension of the mechanical treatment time, the carbon layer spacing of the material is continuously compressed, and a relatively dense coating structure can be formed. The pore structure of the negative electrode material is optimized, the specific surface area is significantly reduced, and the tap density is significantly improved, which is conducive to the improvement of the full battery cycle performance and processing performance. The fast charging performance and cycle performance of Comparative Example 1 deteriorate because the anisotropy of the expanded graphite microcrystal coating layer structure that has not been mechanically treated is high, and its large interlayer spacing makes the coating structure loose and messy, which not only makes the specific surface area of the finished modified graphite material too large and the tap density of the negative electrode material too low, but also the fast charging ability is weak, and the unmodified electron-rich conductor structure is prone to side reactions with the electrolyte during long cycles, resulting in a large amount of active lithium loss, so its cycle performance is significantly deteriorated.
[0189] From the comparison of Examples 6, 8, and 11, it can be found that when the carbonization temperature and the carbonization time are reduced, the fast charging ability of the material is equivalent but the high temperature performance deteriorates; when the carbonization temperature and the carbonization time are increased, the high temperature performance of the material is slightly improved but the fast charging performance deteriorates.
[0190] From the comparison between Examples 6 and 9 and Comparative Example 2, it can be found that when the modified graphite material precursor is not activated after carbonization, its gram capacity, first efficiency, 4C charge rate and cycle performance are significantly reduced.
[0191] By comparing Example 6 with Examples 12-13, it can be found that when the activation temperature is low, the content of oxygen-containing functional groups on the surface of the modified graphite particles will be low. This is because the low temperature leads to a low degree of oxidation reaction, and the reaction energy barrier between water vapor and carbon-based materials is high, so the activation purpose cannot be achieved, and the improvement effect of the capacity and electrical properties of the material is not ideal; when the activation temperature is high, although the content of oxygen-containing functional groups on the surface of the modified graphite particles can be increased, the tap density of the modified graphite particles is significantly reduced and the specific surface area is significantly increased, which indicates that the expansion and pore expansion of oxygen atoms brings about the improvement of fast charging performance, but the rich mesopores and macropore structures make the high temperature performance worse, and the reduction in tap density is not conducive to achieving good dispersion in the material homogenization stage, so the oxygen-containing functional group content of the material should not be too high.
[0192] It can be found from Examples 6 and 14-15 that when the activation temperature is too low or too high, the content of oxygen-containing functional groups on the surface of the modified graphite particles will be low. This is because too low a temperature leads to a small degree of oxidation reaction, and the energy barrier of the reaction between water vapor and carbon-based materials is high, and the activation purpose cannot be achieved. The improvement effect of the capacity and electrical properties of the material is not ideal; when the activation temperature exceeds 1300°C, it is the cracking and detaching temperature of oxygen atoms. Oxygen atoms are continuously detached under high temperature conditions, so the content of oxygen-containing functional groups is significantly reduced, and the carbon layer further shrinks at high temperature, which is not conducive to Li + Rapid deintercalation between carbon layers deteriorates fast charging and cycling performance.
[0193] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0194] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A modified graphite material, characterized in that: The modified graphite material comprises graphite particles and porous graphene sheets coated on the surface of the graphite particles, the surface of the porous graphene sheets has oxygen-containing functional groups, and the mass ratio of the porous graphene sheets to the graphite particles is 0.1-10:
100.
2. The modified graphite material according to claim 1, characterized in that The oxygen-containing functional group includes any one or more of a hydroxyl group, a carboxyl group, a carbonyl group, a keto group and an epoxy group; And / or, based on the total mass of the modified graphite material being 100%, the content of the oxygen-containing functional group is 0.05-2.8%.
3. The modified graphite material according to claim 1 or 2, characterized in that: The average width of the ordered layered nanodomains of the porous graphene sheet is 4-20 nm; and / or, the average thickness of the ordered layered nanodomains of the porous graphene sheet is 0.2-2 nm; And / or, the carbon interlayer spacing of the porous graphene sheet is 0.34-0.46 nm.
4. The modified graphite material according to claim 1 or 2, characterized in that: The volume median particle size of the porous graphene sheet is 0.1-2 μm; And / or, the volume median particle size of the graphite particles is 5-25 μm; And / or, the volume median particle size of the modified graphite material is 8-16 μm.
5. The method for preparing the modified graphite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) ball milling a graphite source to obtain a porous graphene sheet; (2) dispersing the porous graphene sheets, graphite particles and a binder in a solvent for granulation to obtain a modified graphite material precursor; (3) Carbonizing and activating the modified graphite material precursor in sequence to obtain the modified graphite material.
6. The preparation method according to claim 5, characterized in that: The rotation speed during ball milling is 120-900r / min; And / or, the ball milling time is 2-7h; and / or, the carbonization is carried out under an inert gas atmosphere; And / or, the carbonization temperature is 400-1000°C; And / or, the carbonization time is 2-8h; And / or, the activation is carried out in the presence of deionized water, and the mass ratio of the deionized water inflow per minute to the modified graphite material precursor is 0.1-7.2:100; And / or, the activation temperature is 600-1200°C; And / or, the activation time is 1-4h.
7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the porous graphene sheet, the graphite particles and the binder is (0.1-8):(74-99.89):(0.01-18); And / or, the graphite source includes any one or more of expanded graphite, natural flake graphite, artificial graphite and recycled graphite; and / or, the binder comprises any one or more of asphalt, phenolic resin, glucose, sucrose, soluble starch and cyclodextrin; And / or, the solvent includes deionized water and / or ethanol.
8. A negative electrode plate, characterized in that: The negative electrode plate comprises the modified graphite material according to any one of claims 1 to 4 or the modified graphite material prepared by the preparation method according to any one of claims 5 to 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 8.
10. A vehicle, characterized in that: The vehicle includes the lithium-ion battery of claim 9.
Citation Information
Patent Citations
Graphite negative electrode material, preparation method thereof and battery
CN117199363A
Cited By
Negative pole piece, lithium ion battery and electronic equipment
CN119905517A